The Relationship between Refractive Errors and Intraocular Pressure After Adjusting with Central Corneal Thickness - Juwayli, Rabeea Mifath Mohammed; Juwayli, Rabeea Mifath Mohammed; Farag, Adel Abdel Razik; Shalaby, Adel Abd El-Azim; Deen, Sherif Mohammed Sharf El (International Journal of Psychosocial Rehabilitation, 2020)
Background : It is generally accepted that there is an increased prevalence of glaucoma among myopic eyes. One of the reasons as to whyglaucoma should be more frequent in myopic eyes seems to be higher intraocular pressure (IOP) in myopic eyes compared with non-myopic eyes. Aim of the study: This study was aimed to assess the correlation between refractive status and intraocular pressure after adjustment with Central corneal thickness. Patients and Methods : This Prospective cross-sectional study was conducted in Ophthalmology Department at Zagazig University Hospitals. 50 patients with refractive errors, divided in 2 groups 25 are myopic eyes and 25 are hypermetropic eyes. During the period from April to December 2019, Before the experiment, all patients underwent a complete ophthalmic examination, including visual acuity, manifest refraction, comprising refraction, slit lamp examinations and corneal topography. Results: There was a statistical significant negative correlation between spherical equivalent and IOP and AIOP (r=-0.728 and r=- 0.499, P-value <0.05), regarding central corneal thickness, there was statistically significant negative correlation between AIOP and CCT(r=-0.419, p-value <0.05)but there was positive correlation between CCT and IOP(r=0.521, p-value<0.05). Conclusions: The myopic refractive error and the intra-ocular pressure seem to have a significant correlation as such that with the increase of myopic refractive error there was increase of the intra-ocular pressure. This findings support the hypothesis that the relationship between glaucoma and myopia might be pressure mediated.